Lhx8 ablation leads to massive autophagy of mouse oocytes associated with DNA damage - D'Ignazio, Laura; Michel, Marc; Beyer, Melissa; Thompson, Kassimier; Forabosco, Antonino; Schlessinger, David; Pelosi, Emanuele (Biology of reproduction, 2018)
Following proliferation of oogonia inmammals, great numbers of germ cells are discarded, primarily by apoptosis, while the remainder form primordial follicles (the ovarian reserve) that determine fertility and reproductive lifespan. More massive, rapid, and essentially total loss of oocytes, however, occurs when the transcription factor Lhx8 is ablated—though the cause and mechanism of germ cell loss from the Lhx8-/- ovaries has been unknown. We found that Lhx8-/- ovaries maintain the same number of germ cells throughout embryonic development; rapid decrease in the pool of oocytes starts shortly before birth. The loss results from activation of autophagy, which becomes overwhelming within the first postnatal week, with extracellular matrix proteins filling the space previously occupied by follicles to produce a fibrotic ovary. Associated with this process, as early as a few days before birth, Lhx8-/- oocytes failed to repair DNA damage—which normally occurs when meiosis is initiated during embryonic development; and DNA damage repair genes were downregulated throughout the oocyte short lifespan. Based on gene expression analyses and morphological changes, we propose a model in which lineage-restricted failure of DNA repair triggers germ cell autophagy, causing premature depletion of the ovarian reserve in Lhx8-/- mice. Summary Sentence Ablation of Lhx8 causes premature loss of germ cells by autophagy associated with impairment of DNA damage repair during meiosis.